Eyesores - Shade, Eric, 1970- (Book collections on Project MUSE., 2003)
"These eleven interrelated stories follow strands of hope and nostalgia that bind together, or fence off, the people of Windfall, Eric Shade's fictional western Pennsylvania community. In the title story, a group of unskilled laborers rerun memories of youth as they race against the dark to demolish the town's drive-in theater. A chain restaurant will take its place. Naomi dumps Dwight at the altar in "Hoops, Wires, and Plugs," but then Dwight fritters away the shamed agitation that could have propelled him beyond Windfall's stunting gravitational pull. In the final story, "Souvenirs," small-time hoods Paxson and Gus do what so many in Windfall can't: get out of town. They're off to Pittsburgh and a contract killing they hope will kick off a more rewarding life of crime."--Jacket